Association of diabetes and tuberculosis: impact on treatment and post-treatment outcomes. Issue 3 (18th December 2012) - Jiménez-Corona, María Eugenia; Cruz-Hervert, Luis Pablo; García-García, Lourdes; Ferreyra-Reyes, Leticia; Delgado-Sánchez, Guadalupe; Bobadilla-del-Valle, Miriam; Canizales-Quintero, Sergio; Ferreira-Guerrero, Elizabeth; Báez-Saldaña, Renata; Téllez-Vázquez, Norma; Montero-Campos, Rogelio; Mongua-Rodriguez, Norma; et al.
Abstract : Objective: To determine the clinical consequences of pulmonary tuberculosis (TB) among patients with diabetes mellitus (DM). Methods: We conducted a prospective study of patients with TB in Southern Mexico. From 1995 to 2010, patients with acid-fast bacilli or Mycobacterium tuberculosis in sputum samples underwent epidemiological, clinical and microbiological evaluation. Annual follow-ups were performed to ascertain treatment outcome, recurrence, relapse and reinfection. Results: The prevalence of DM among 1262 patients with pulmonary TB was 29.63% (n=374). Patients with DM and pulmonary TB had more severe clinical manifestations (cavities of any size on the chest x-ray, adjusted OR (aOR) 1.80, 95% CI 1.35 to 2.41), delayed sputum conversion (aOR 1.51, 95% CI 1.09 to 2.10), a higher probability of treatment failure (aOR 2.93, 95% CI 1.18 to 7.23), recurrence (adjusted HR (aHR) 1.76, 95% CI 1.11 to 2.79) and relapse (aHR 1.83, 95% CI 1.04 to 3.23). Most of the second episodes among patients with DM were caused by bacteria with the same genotype but, in 5/26 instances (19.23%), reinfection with a different strain occurred. Conclusions: Given the growing epidemic of DM worldwide, it is necessary to add DM prevention and control strategies to TB control programmes and vice versa and to evaluate their effectiveness. The concurrence of both diseases potentially carries a risk of global spreading, with serious implications for TB control and the achievement of the United Nations Millennium Development Goals.